Constraints in the control of animal trypanosomiasis by cattle farmers in coastal savannah of Ghana: Quality aspects of drug use - Esena, Reuben K. (Journal of Research in Biology, 2013)
Cattle trypanosomiasis is a major constraint to livestock development in Ghana and is demonstrated by the fact that cattle farmers treat the disease by themselves. The main objective of this study is to identify the constraints associated with the control of trypanosomiasis by cattle farmers. To identify the constraints, 250 herdsmen were interviewed on the use of trypanocides to treat cattle trypanosomiasis. The interview focused on treatment procedures such as knowledge of diagnosis, trypanosomiasis treatment procedures, dilutions, injection techniques, volume of trypanocides used and prophylaxis use. The data were supplemented by relevant records and information from the following sources: Department of Veterinary Technical officers (Community Animal Health/Frontline Staffs), District veterinary doctors and the National Head of Tsetse and trypanosomiasis Control Unit. To empirically estimate the marginal effect of constraints affecting the control of trypanosomiasis, multiple regression equations were run on the PC-SPSS version 16 programme by Ordinary Least Squares (OLS) analysis. In this analysis, the “general to specific” approach of Hendry as found by Koutsoyiannis (1977) was adopted in order to arrive at a coherent regression results. This provided a reliable means of recommending appropriate and effective control strategies and good drug services for traditional husbandry systems. In this research, certain factors were identified as affecting cattle production. They are, inappropriate dosage of Berenil® used by farmers, selective treatments adopted, pour-on techniques and lack of extension training. Others were the criteria for treatments, inappropriate treatment intervals, underdosing of Berenil® used, and cost of inputs and services. Some others were injection techniques, lack of knowledge of trypanocides and dilution of drugs. These are factors that affect productivity and need to be addressed by policy makers especially by the Veterinary department to improve drug use by herdsmen.